Notice of the discovery of an ancient boat, of singular construction, on the banks of the Clyde (Proceedings of the Society of Antiquaries of Scotland, 1854)
Corresponding member John Buchanan sent a notice that a canoe had been uncovered on the banks of the Clyde. This is the sixteenth canoe to be discovered in this area. Buchanan describes how the construction of this canoe differed from the previous examples and notes that the positioning that the boat was uncovered in suggests it was overturned in a storm. The canoe did not survive the removal from the position it was found in. Buchanan observed a set of irregular perforations on the side of the canoe and asks the Fellows of the Society for their input on what these might be.